Nucleic acids and protein synthesis: Part C; V20 - Moldave, Kivie; Ed. Grossman, Lawrence; Ed (Methods in enzymology, 1971)
A history of Israel's Defence Force describing the conditions that forced it to develop skilled fighters and analyzing the long conflict with the Arabs which in 1967 resulted in the Six-Day War.